Rancang Bangun Alat Mobile Smart Trash Bin Menggunakan Raspberry Pi - asep kurniawan; Rachman Hanafi; Muhammad Arlan Ardiawan; Indra Hermawan; Albarofi Fierelio Kinandes Sumarsono (Politeknik Caltex Riau, 2023)
People's living standards are increasing with the development of the global economy, so that the production of domestic waste is increasing from year to year. However, in waste processing there is still a problem of mixing waste in landfills where hazardous waste is still mixed so that it can cause the spread of covid. Currently the trend is starting to shift to smart devices that use the Internet of Things to solve common problems such as waste management problems. In this study, a Mobile Smart Trashbin is proposed which can reduce direct interaction because it has an automatic opening and closing feature, can sort waste into hazardous and harmless, can transmit waste weight data, and can be controlled remotely and equipped with livestream. The developed system is tested by the methods of functionality testing, performance testing, and connectivity testing. Functionality testing gives the result that the whole system can work. Performance testing on the ultrasonic sensor results in an accuracy rate of 97.18%, the MG995 servo motor is at 100%, the weight sensor has an accuracy rate of 98.65%, and the use of batteries in standby can work for 13 hours 3 minutes 40 seconds and in a running state can work for 1 hour 56 minutes 42 seconds. The connectivity test of the average delay of robot control when given a command is 103.4ms, and the delay in sending waste weight data is 112.8ms.